(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
For the first time, detailed biographical data on the military and administrative service of Major General Georgy Arandarenko (1846-1908), military governor and commander of the Fergana region of the Turkestan Governor-General, an outstanding scientist and statesman of the Russian Empire in the second half of the XIX century, one of the first researchers of the Bukhara Khanate and Afghan Turkestan. The data on his ancient Polish gentry origin from the Yaranda clan of the Brudze coat of arms of Pomyan, about his Zaporozhye ancestors, whose famous Известия НАН КР, 2021, № 1 73 representatives were the Cossack hetmans Timofey Arandarenko and Taras Shakilo are given. His scientific, ethnographic and statistical studies of Gissar, Karatygin, Darvaz, the eastern part of the Bukhara Khanate, winter trips to the glaciers of Zaravshan are considered. The stages of G.A. Arandarenko’s service in Turkestan, his powers and reasons for resignation are discussed in detail. A comprehensive analysis of his personality and contribution to the conquest and administration of Turkestan is given.